Faktor Risiko Pasien Acute Limb Ischemia - Admadiani, Fhahira Rizkhika; Ekoputranto, J Nugroho; Soebroto, Heroe; Subagjo, Agus (Cerdika: Jurnal Ilmiah Indonesia, 2022)
Acute Limb Ischemia (ALI) is a classification of peripheral arterial disease that causes decreased blood flow to the extremities, with onset within 2 weeks and characterized by 6 'P's, namely pallor, pain, perishing cold, pulseless, paralysis, and paresthesia. This can be identified through several risk factors, including: diabetes, smoking, gender, high blood pressure, age,hyperlipidemia, atrial fibrillation (AF) and diabetes. This study aims to identify risk factors in ALI patients. Hospital identification. Soetomo Surabaya Period January 2016 – March 2019. This study uses a total sampling technique. This study uses a descriptive cross sectional method with medical record instruments and direct interviews with patients. Twenty-five (25) patients were known to have ALI (14 males and 11 females), and the age of the patients ranged from 65 to 69 years (20%). The causes of risk included a history of smoking obtained from 10 subjects (40%), a history of hypertension in 7 subjects (28%), a history of stage 1 hypertension, a history of diabetes mellitus with the highest blood glucose test value > 126 mg/dl up to 10 people. . (62.5%), with a history of hyperlipidemia, with total cholesterol within normal limits of up to 4 (66.7%), LDL in the normal range of not more than 3 (60%), and HDL with 2 with low HDL values (40%). ), and the highest triglyceride levels were within the normal range. Electrocardiographic examination revealed 7 patients (28%) with atrial fibrillation. Most of the ALI patients in this study were aged between 65 and 69 years and were male. Most ALI patients in this study were 65-69 years old and males. The most common risk factors for ALI patients were hypertension, diabetes mellitus, and hypercholesterolemia.